Safety Implications of GNSS Signal Interference at Zilina Airport - Andrej Novak; Alena Novak Sedlackova; Anna Stelmach; Doris Novak (Communications - Scientific letters of the University of Zilina, 2020)
The paper deals with the issue of GNSS interference and its subsequent impact on airport approach procedures. It discusses the problem of GNSS signal interference and interference identification on a practical example of a small regional airport in Zilina, located close to the highway, through research aimed at its identification, a proposal for the location of a monitoring station and subsequent practical verification. The paper seeks to analyse and provide recommendations for enhancing safety and reliability in GNSS approaches. Given the need to develop the air transport, it is important to ensure the safety and continuity of service provision at small regional airports. The GNSS approach at airports with insufficiently equipped navigation infrastructure seems to be one of the most suitable. Introduction of the GNSS interference monitoring in the final instrument approach phase would increase the safety and reliability of the flight.